EVALUATION OF THE EFFECT OF FLAVONOID EXTRACT OF Ginkgo biloba LEAVES AND GLIMEPHAN ON OXIDATIVE STRESS AND RETINA DEGENERATION IN DIABETIC MALE RABBITS INDUCED BY STREPTOZOTOCIN - Wasan A. Jawad; Muna H. AL-Saeed (Basrah Journal of Veterinary Research)
This study was carried out in animal house of Collage of VeterinaryMedicine/ University of Basrah. An attempt has been done to induce diabetic bystreptozotocin in male rabbits and investigation of the diabetes was induced oxidativestress and retina degeneration. Moreover, the purpose of this study was to isolate andevaluate the ameliorating effect of flavonoid extract of Ginkgo biloba leaves andglimephan in the prophylaxes or delay the development of diabetic retinadegeneration and scavenging free radical induced oxidative stress and diabetic retinadegeneration in male rabbits.The study was done on (32) adult male rabbits, theirweight ranged between (2000-2500g) and aged between 7-8 months. The malerabbits were divided randomly into four groups, each group consists of eight rabbitsas the following:Group1:- Male rabbits at (Negative controls(-ve)) administrated normal saline1mlorally for 30 days.Group2:- Male rabbits at(Positive control(+ve)) were given streptozotocin(65mg/kg B.W. dissolve in sodium citrate I.V.) for two days and remain for 30 days Group3:- Male rabbits were given streptozotocin( 65mg/kg B.W. dissolve insodium citrate I.V.) for two days, then treated with flavonoid extract of Ginkgo bilobaleave (500mg/kg B.W. orally administration) for 30days.Group4:- Male rabbits were given streptozotocin (65mg/kg B.W. dissolve insodium citrate I.V.) for two days, then treated with glimphan drug (0.1mg/kg orallyadministration) for 30 days.At the end of the experimental period, the blood samples were collected from heartby cardiac puncture for isolated serum and analysis biochemical parameters such asglucose, insulin, malonaldehyd (MDA),Superoxide dismutase (SOD) and glutathioneperoxidase (GPx) concentrations and lipid profile. The results revealed a significant(P≤0.05) decrease of body weight, body weight gain and HDL concentrations inserum diabetic rabbits control(+ve) compared with control(-ve) while the resultsshowed a significant (P≤0.05) increase the glucose, insulin cholesterolLDL,VLDL,MDA and GPx concentrations in serum diabetic male rabbitscontrol(+ve) compared with control(-ve). The results obtained a significant decrease(P≤0.05) in body weight, body weight gain, SOD and HDL concentrations in serumdiabetic male rabbits control(+ve). While male rabbits treated with flavonoid extractof Ginkgo biloba the results observed a significant (P≤0.05) increase in body weightand body weight gain compared with control(+ve). Whereas the results wererevealed a significant(P≤0.05)decrease of glucose, insulin, cholesterol, LDL,VLDL.MDA and GPx concentration rabbits treated with flavonoid extract of Ginkgo bilobaleave compared with control(+ve) and glimephan also in addition, this extractimproved the retina degeneration.Histological examination observed manypathological changes in pancreas and retina in diabetic group but in treated withflavonoid extract of Ginkgo biloba, the histological changes were near to the normalstatus. It is concluded that good anti-diabetic activity, hypoglycemia effect andregeneration of retina. Based on these results, we suggested the possible utilization ofGinkgo biloba as a therapy to prevent diabetic complication and improved the retinadegeneration compared with another treated such as glimephan drugs.